BIMBINGAN DAN KONSELING KRISTEN BAGI PEMUDA KRISTIANI MENURUT 1 TIMOTIUS 4:12 BERDASARKAN TEORI PSIKOLOGI HUMANISTIK CARL ROGERS DANABRAHAM MASLOW - Darmawati Kaya'; Alda Septrianty, Arniati Palino, Destriani Sesa, Flexi Keris Touver (Adisam Publisher, 2025)
This research aims to explore the application of Christian guidance and counseling for Christian youth based on 1 Timothy 4:12, using the humanistic theory approach of Carl Rogers and Abraham Maslow. Through this approach, the study aims to identify how the Biblical principles of faith, love, sanctity, and spiritual growth can be integrated with concepts such as empathy, unconditional acceptance, and self- actualization from humanistic theory. The research method employed is a literature review, analyzing relevant literature on Christian guidance and counseling, humanistic theory, and Biblical verses. The findings of this research are expected to provide a deeper understanding of the potential integration between Biblical principles and humanistic theory in the context of Christian guidance and counseling for Christian youth, as well as its practical implications in aiding Christian youth to achieve better personal growth and spiritual well-being.